Porous Polylactide Microparticles as Effective Fillers for Hydrogels - Yuriy D. Zagoskin; Yana E. Sergeeva; Yuliya S. Fomina; Daniil V. Sukhinov; Sergey N. Malakhov; Egor O. Osidak; Elena A. Khramtsova; Pavel M. Gotovtsev; Sergei N. Chvalun; Timofei E. Grigoriev (Biomimetics, 2023)
High-strength composite hydrogels based on collagen or chitosan–genipin were obtained via mixing using highly porous polylactide (PLA) microparticles with diameters of 50–75 µm and porosity values of over 98%. The elastic modulus of hydrogels depended on the filler concentration. The modulus increased from 80 kPa to 400–600 kPa at a concentration of porous particles of 12–15 wt.% and up to 1.8 MPa at a filling of 20–25 wt.% for collagen hydrogels. The elastic modulus of the chitosan–genipin hydrogel increases from 75 kPa to 900 kPa at a fraction of particles of 20 wt.%. These elastic modulus values cover a range of strength properties from connective tissue to cartilage tissue. It is important to note that the increase in strength in this case is accompanied by a decrease in the density of the material, that is, an increase in porosity. PLA particles were loaded with C-phycocyanin and showed an advanced release profile up to 48 h. Thus, composite hydrogels mimic the structure, biomechanics and release of biomolecules in the tissues of a living organism.